Penegakan Hukum Terhadap Tindak Pidana Penodaan, Penyalahgunaan, Dan Penistaan Agama Hindu Di Bali - I Putu Eka Saputra; Karolus Kopong Medan; Bhisa Vitus Wilhelmus (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This research is motivated by the increasing number of cases related to the use of Hindu symbols and teachings, which have provoked public reaction and the potential for social conflict in Bali. This issue is important because it relates to legal certainty in the application of Article 156a of the Criminal Code and the protection of religious values. This study aims to analyze the elements of the crimes of blasphemy, misuse, and defamation and examine the factors influencing law enforcement against these crimes in Bali. The research method used is empirical juridical with a normative and sociological approach, through literature review and interviews, followed by qualitative analysis. The results indicate that the objective elements in Article 156a of the Criminal Code are generally met, particularly regarding the elements of "in public" and the existence of an act or statement. However, proving the subjective element of intent (dolus) requires caution because it is related to the perpetrator's intent. Furthermore, law enforcement is influenced by the multi-interpretable substance of the law, the legal structure, and the Balinese legal culture, which tends to prioritize customary resolution. Therefore, law enforcement against the crime of blasphemy against Hinduism in Bali is not only based on positive legal provisions but is also influenced by the social and cultural conditions of the community. Therefore, judicious application of the law and synergy between law enforcement officials and customary institutions are required.